Mechanistic insights into vascular biology via methyltransferase-like 3-driven N6-adenosine methylation of RNA - Zhang, Deshuang; Gou, Zhixian; Qu, Yi; Su, Xiaojuan (Frontiers in Cell and Developmental Biology, 2025)
Recent advancements in the mechanistic comprehension of vascular biology have concentrated on METTL3-mediated N6-methyladenosine modification of RNA, which modulates a spectrum of RNA functionalities with precision. Despite extensive investigations into the roles and mechanisms of METTL3 within vascular biology, a holistic review elucidating their interconnections remains absent. This analysis endeavors to meticulously scrutinize the involvement of METTL3 in both the physiological and pathological paradigms of vascular biology. The findings of this review indicate that METTL3 is indispensable for vascular development and functionality, predominantly through its regulatory influence on pericytes, endothelial cells, vascular smooth muscle cells, and hematopoietic stem cells. Conversely, aberrant METTL3 activity is implicated as a risk factor, diagnostic biomarker, and therapeutic target for vascular pathologies. This comprehensive review offers an exhaustive synthesis of METTL3’s role in vascular biology, addressing existing knowledge gaps and serving as an essential reference for future research and potential clinical applications.